2020
DOI: 10.1002/jgh3.12408
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib as second‐line treatment option after failure of lenvatinib in patients with unresectable hepatocellular carcinoma

Abstract: Background and Aim Currently, there is no molecular‐targeted agent that has demonstrated evidence of efficacy in patients with unresectable hepatocellular carcinoma (u‐HCC) who have developed resistance to treatment with lenvatinib (LEN). In this real‐world study, we aimed to investigate the therapeutic effect and safety of sorafenib (SOR) in patients with u‐HCC after progression on treatment with LEN. Methods (Patients) and Results A total of 13 patients with u‐HCC (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…8,9 In contrast, the therapeutic efficacy and safety of SOR or RAM after disease progression following LEN treatment has been reported in small cohort studies. 10,11 These findings indicate the feasibility of sequential MTA therapies for the treatment of u-HCC. However, the REFLECT study was conducted before second-line MTA therapy became fully available in practice; the patients in that study were recruited before 2015, and November 13, 2016 was set as the data cut-off date.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…8,9 In contrast, the therapeutic efficacy and safety of SOR or RAM after disease progression following LEN treatment has been reported in small cohort studies. 10,11 These findings indicate the feasibility of sequential MTA therapies for the treatment of u-HCC. However, the REFLECT study was conducted before second-line MTA therapy became fully available in practice; the patients in that study were recruited before 2015, and November 13, 2016 was set as the data cut-off date.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, the effectiveness of treatment with LEN after progression following SOR treatment has been reported in retrospective studies 8,9 . In contrast, the therapeutic efficacy and safety of SOR or RAM after disease progression following LEN treatment has been reported in small cohort studies 10,11 . These findings indicate the feasibility of sequential MTA therapies for the treatment of u‐HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for second-line treatment after sorafenib is well established, and three agents-regorafenib, ramucirumab, and cabozantinib-have shown clinical benefits in phase 3 trials. [7][8][9] In contrast, unlike sorafenib, second-line treatment after lenvatinib has not been firmly established-several studies have been reported [28][29][30] but were based on a small number of patients, leaving insufficient evidence. In addition, there were a few options for subsequent treatment in the lenvatinib group because cabozantinib was not a treatment option during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason why the sorafenib group had more patients to receive subsequent treatment might be related to the insurance system for second-line treatment. Unlike sorafenib, there is no evidence for the effectiveness of molecularly targeted agents in advanced HCC after progression following lenvatinib treatment [ 29 ]. However, sequential treatment with sorafenib-regorafenib is covered by the National Health Insurance System of Korea after RESORCE trial, and in a previous study, 26-month survival was reportedly possible [ 30 ].…”
Section: Discussionmentioning
confidence: 99%